Locked into the ivory tower? Mobility and entrepreneurship among Swedish academics - Olof Ejermo (European Regional Science Association (ERSA), 2010)
Empirical evidence clearly shows that Sweden performs well in terms of formal science and technology indicators such as research and development, patenting and publications. Among academics recent show that Swedish academics patent extensively by international comparison. Nevertheless, many notions exist that Sweden underperforms in terms of innovation ("the Swedish paradox") and level entrepreneurship in relation to her strong inputs. Innovation systems approaches as well as spillover literature stress the importance of interaction and transfer of knowledge across organizations in a society to attain higher social returns to innovation investments. In such processes, labor mobility between firms and spin-off entrepreneurship has been singled out as important transfer mechanisms in recent studies of the mechanisms behind such interaction. This paper examines new evidence as to the extent that academics are part of a general Swedish problem or contribute to more entrepreneurship and labor mobility. A database of all Swedish working individuals is used to examine patterns and causal mechanisms behind mobility and firm formation comparing patterns found for the academic sector with that of other sectors. Preliminary evidence reveals that persons working in Swedish academia are less mobile and less entrepreneurial than in all other sectors. Controlling for individuals factors indicates that higher education and PhD education contribute positively to mobility and entrepreneurship. The only two exceptions are for employees in primary sectors, where this tendency is reversed, and for PhDs in academia which are much less entrepreneurial than other PhDs. Business income among academics are also very low, which indicate that 'side activities' such as consultancy for the business sector is rare. Taken together, the scientific norm tends to rule in academia despite much policy discussion that its sector's employees should interact much with the rest of society.
Keywords: 330